Gratitude as a Protective Factor for Cyberbullying Victims: Conditional Effects on School and Life Satisfaction - Oriol, Xavier (2021)
Recently, studies linking the emotion of dispositional gratitude to cyberbullying have attracted attention. However, this is still a seminal research area that requires further scientific studies. Through longitudinal data, this study aims to analyze the mitigating effect of gratitude on cybervictimization and two indicators of adolescent subjective well-being, namely school and life satisfaction. To this end, 221 adolescents attending private schools in Peru (age: mean (M) = 12.09; standard deviation (SD) = 0.89) were selected to respond to a self-administered questionnaire in two waves that were six months apart. Descriptive data show that 27% of cybervictims also suffer other types of traditional bullying. The overlaps between forms of bullying contribute to higher probabilities of experiencing low school and life satisfaction compared to non-victims after six months. The results of the moderation analysis show that experience high gratitude help students to maintain stable levels of life satisfaction regardless of the prevalence of cyberbullying after six months The results are discussed in terms of the relevance of fostering gratitude from early ages.